2022
DOI: 10.1007/s00704-022-04272-5
|View full text |Cite
|
Sign up to set email alerts
|

Probability distribution characteristics of summer extreme precipitation in Xinjiang, China during 1970–2021

Abstract: Based on the daily precipitation data of 96 stations in Xinjiang, China, from 1970 to 2021, the trend of summer extreme precipitation indices and their regional characteristics are analyzed. The generalized extreme value (GEV) model is used to investigate the probability distribution characteristics of summer extreme precipitation indices in northern, southern, and eastern Xinjiang. The results show that (1) The summer maximum 1-day precipitation (RX1day) and maximum 5-day precipitation (RX5day) of most statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Hu observed a declining trend in the number of overall cumulative dry days (CDD) in Xinjiang [76]. However, in this study, the CDD showed a rising tendency, which contradicts the general pattern observed in Xinjiang, and compared to northern Xinjiang, there are fewer RX1d and RX5d events with weaker intensity in the Tarim Basin, while the CDD events are the opposite [77]. Under RCP4.5 and RCP8.5 scenarios, Zhang concluded that the CDD in Central Asia is expected to increase slightly in the 21st century [78], and persistent drought in southern Xinjiang is also expected to intensify [79], aligning with the conclusions drawn from this research.…”
Section: Changes In the Extreme Climate Indicescontrasting
confidence: 99%
“…Hu observed a declining trend in the number of overall cumulative dry days (CDD) in Xinjiang [76]. However, in this study, the CDD showed a rising tendency, which contradicts the general pattern observed in Xinjiang, and compared to northern Xinjiang, there are fewer RX1d and RX5d events with weaker intensity in the Tarim Basin, while the CDD events are the opposite [77]. Under RCP4.5 and RCP8.5 scenarios, Zhang concluded that the CDD in Central Asia is expected to increase slightly in the 21st century [78], and persistent drought in southern Xinjiang is also expected to intensify [79], aligning with the conclusions drawn from this research.…”
Section: Changes In the Extreme Climate Indicescontrasting
confidence: 99%
“…Over the period from 1960 to 2021, the average annual temperature in Xinjiang ranged from −20 • C to 17 • C, with an average annual precipitation level of 156 mm. Precipitation in northern Xinjiang generally surpasses that in the southern region, and mountainous areas receive greater amounts of precipitation compared to the basin areas [40][41][42].…”
Section: Study Areamentioning
confidence: 99%